Intra‐ and interday repeatability of peripheral arterial function: suitability and potential limitations. (October 2016) - Del Bo', Cristian; Deon, Valeria; Porrini, Marisa; Campolo, Jonica; Parolini, Marina; Riso, Patrizia
Abstract: Objective: This study aimed to investigate the inter‐and intraday repeatability of RHI measured by Endo‐PAT in healthy volunteers. Methods: Interday RHI repeatability was tested in two consecutive days in a group of 31 male subjects. Intraday repeatability was investigated at baseline and after 2 and 4 hour in a group of 16 volunteers. Data were evaluated by analysis of variance. Bland‐Altman plot, CV, CR, and ICC were measured. Results: While interday RHI repeatability was found to be reliable (CV: 6.0%; CR: 0.51; ICC: 0.77), multiple evaluations within the same day significantly ( P <.001) affected RHI (repeatability of the measurement ‐CV: 18.8%; CR: 1.26; ICC: 0.48). In particular, a significant increase in RHI occurred at 4 hour compared to 2 hour (+16.8%; P <.05) and to baseline (+30.1%; P <.05). Conclusions: RHI showed good interday but poor intraday repeatability. Multiple evaluations increased RHI especially in subjects with endothelial dysfunction who improved or reversed their impairment. These results show the potential limitations of multiple Endo‐PAT measurements within the same day and the importance of standardizing the protocols before RHI evaluations.